PENGARUH KUALITAS PROGRAM CUSTOMER RELATIONS TERHADAP TINGKAT KEPERCAYAAN PELANGGAN - Denada Lubis (Jurnal Visi Komunikasi, 2019)
Kuningan City Mall is one of the property industry fields, namely a shopping mall that was established in 2012 in South Jakarta. Along with the development of the retail service industry, Kuningan City Mall is well aware of the importance of quality customer relations programs to increase customer trust which leads to satisfaction and profitability. In realizing customer trust requires a good or positive experience from a company. This experience can be realized through good communication in customer relations program activities, in this case Kuningan City Mall develops a "K-Passport" program to improve the quality of the customer relations program and enhance a sense of trust in the eyes of its customers. Quantitative research with explanative type was chosen because researchers wanted to measure the influence of the quality of the customer relations program on the level of customer trust. While the method used is survey method. Samples were taken according to the number of 100 respondents. The Quality of Program Customer Relationship variable regression coefficient (XI) is 0.896, meaning that if the other independent variables are fixed, then the Customer Trust Level (Y) will increase by 0.896. The quality of the Customer Relations Program is able to explain the influence of 87.4% on the dependent variable (Level of Customer Trust).